PENGARUH LIKUIDITAS DAN PROFITABILITAS PADA STRUKTUR MODAL PERUSAHAAN RETAIL DI BEI - Mutiara Cindy Ramadhani; Muhadjir Anwar (Universitas Islam Kadiri, 2021)
Abstract This study was conducted to determine the effect of liquidity and profitability on the capital structure of retail companies listed on the Indonesia Stock Exchange (BEI) for the period 2017-2019. The author approached quantitative data in the form of financial reports obtained through www.idx.co.id. The researcher approach purposive sampling method and obtained observation data of 54 retail companies that have met the criteria to determining the samples. The technique of analyzing of data, the author use path analysis with apply SPSS program system. Refers to the test results indicated that the liquidity variable (current ratio) has a negative and significant effect on capital structure (debt to equity ratio), liquidity (current ratio) has a positive and significant effect on profitability (ROA), and profitability (ROA) has a positive and significant effect on capital structure (debt to equity ratio). The results of this study indicate that the role of the profitability variable as a intervening is able to intervening the effect of liquidity on capital structure through profitability. Keywords: Capital Structure, Liquidity, Profitability.